Environmental detection and spreading of mpox in healthcare settings: a narrative review - Taha, Amira Mohamed; Katamesh, Basant E.; Hassan, Abdul Rhman; Abdelwahab, Omar Ahmed; Rustagi, Sarvesh; Nguyen, Dang; Silva-Cajaleon, Kenneth; Rodriguez-Morales, Alfonso J.; Mohanty, Aroop; Bonilla-Aldana, D. Katterine; Sah, Ranjit (Frontiers in Microbiology, 2023)
Monkeypox virus (MPXV), which causes Monkeypox (Mpox), has recently been found outside its usual geographic distribution and has spread to 114 different nations. The World Health Organization (WHO) designated the epidemic a Public Health Emergency of International Concern (PHEIC). Humans are at risk from MPXV's spread, which has raised concerns, particularly in the wake of the SARS-CoV-2 epidemic. The risk of virus transmission may rise due to the persistence of MPXV on surfaces or in wastewater. The risk of infection may also increase due to insufficient wastewater treatment allowing the virus to survive in the environment. To manage the infection cycle, it is essential to investigate the viral shedding from various lesions, the persistence of MPXV on multiple surfaces, and the length of surface contamination. Environmental contamination may contribute to virus persistence and future infection transmission. The best possible infection control and disinfection techniques depend on this knowledge. It is thought to spread mainly through intimate contact. However, the idea of virus transmission by environmental contamination creates great concern and discussion. There are more cases of environmental surfaces and wastewater contamination. We will talk about wastewater contamination, methods of disinfection, and the present wastewater treatment in this review as well as the persistence of MPXV on various environmental surfaces.